FIRM CHARACTERISTICS AND EARNING MANAGEMENT: MODERATING ROLE OF OWNERSHIP STRUCTURE - Ashiq, Anam; Guoxing, Zhang; Hussain Tabassam, Aftab; Waheed, Dr. Abdul (The journal of contemporary issues in business and government, 2022)
Prior studies examine the influence of Firm characteristics and ownership structure on earning management with competing interests. This research investigates the inconsistent results with a proposed framework through the interaction effect of ownership structure (concentrated ownership and institutional ownership) on the relationship between Firm characteristics (firm size and leverage) and earning management. The study carried out a test using a sample of 139 firms listed on Pakistan stock exchange from 2008-2019. This study’s tests are carried out using the Stata programme and the fixed effect panel least squares regression model. The results indicates a negative and significant impact of concentrated ownership on earning management while, firm size, leverage and institutional ownership shows insignificant relationship with earning management. Additionally, the results seem to indicate that concentrated ownership diminished the influence of firm size on earning management. Moreover the relationship between business characteristics and earning management is also unaffected by institutional ownership.This is perhaps because most businesses in Pakistan are family-owned and concentrated.